THE EFFECT SUCCESS OFOVAPRIM, hCG AND COMBINATION ON SPAWNING LELAN BARB(Osteochilus pleurotaenia Blkr) - Bahtera Sanjaya Sitepu; Hamdan Alawi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe aim of this research was to determine the effect of ovaprim, hCG and their combination on spawning success of lelan barb(Osteochilus pleurotaenia Blkr). This research was conducted from 6 September -27 october 2019 at the Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty, Riau University.The method used was an experimental method with a Completely RandomizedDesign (CRD)with four treatments and three replications.The treatments wereP0 (NaCl physiology 0,9%/kg of body weight), P1 ( Ovaprim 0,6 mL/kg of body weight), P2 (hCG 0,5 900 IU/ kg of body weight), and P3 (Ovaprim 0,5 mL/kg + hCG 550 IU/kg of body weight).The best result showed that treatment of P1 (Ovaprim 0,6 ml/kg)was turn of latencytime (6.03 hours), amount eggs strip (174 eggs/g gonads), egg maturition rate (81%), Ovisomatic Index (11,21%), fertility rate (21,68%), hatching rate (77,28%) and survival rate of 5 days larva (81,17%). The water quality parameters during research was in optimal temperature 280 C, pH 6 and dissolved oxygen 3,77- 5,24 ppm. Keywords :Osteochilus pleurotaenia Blkr, Ovaprim, hCG, Spawning